Nitric oxide sensing in plants is mediated by proteolytic control of Group VII ERF transcription factors - Gibbs, Daniel J.; Md Isa, Nurulhikma; Movahedi, Mahsa; Lozano-Juste, Jorge; Mendiondo, Guillermina M.; Berckhan, Sophie; Marín-de la Rosa, Nora; Vicente Conde, Jorge; Sousa Correia, Cristina; Pearce, Simon P.; Bassel, George W.; Hamali, Bulut; et al. (Elsevier, 2014)
Nitric oxide (NO) is an important signaling compound in prokaryotes and eukaryotes. In plants, NO regulates critical developmental transitions and stress responses. Here, we identify a mechanism for NO sensing that coordinates responses throughout development based on targeted degradation of plant-specific transcriptional regulators, the group VII ethylene response factors (ERFs). We show that the N-end rule pathway of targeted proteolysis targets these proteins for destruction in the presence of NO, and we establish them as critical regulators of diverse NO-regulated processes, including seed germination, stomatal closure, and hypocotyl elongation. Furthermore, we define the molecular mechanism for NO control of germination and crosstalk with abscisic acid (ABA) signaling through ERF-regulated expression of ABSCISIC ACID INSENSITIVE5 (ABI5). Our work demonstrates how NO sensing is integrated across multiple physiological processes by direct modulation of transcription factor stability and identifies group VII ERFs as central hubs for the perception of gaseous signals in plants.